Identification Of Density Settlements In Balikpapan City - Agus Fitrianto; Rilia Rigina Mahargamitha (Jurnal Perencanaan Wilayah, 2022)
Settlements that grow irregularly with a high population density indicate the community's quality of life and survival. Dense settlements without proper supervision and planning will make the face of the city become. This study aims to (1) identify the areas in Balikpapan City that are the most vulnerable, (2) assess the slum status of the area, (2) assess the slum status of the analysis using the Identification Guidelines. Permuh Metropolitan City Support Area with Economic Vitality Criteria and Non-Economic Vitality Criteria for you, the most populous city of Balikpapan. (3) formulate priorities for handling the most densely populated areas. The study found that the Karang Rejo sub-district may be an area with a total assessment weight of 430. The Non-Economic Vitality Criteria score is 340, then the Economic Vitality criteria score is 90. Property development management approaches are needed urgently in the Karang Rejo sub-district area.